Structural determinants of subtype selectivity and functional activity of angiotensin II receptors. Issue 4 (15th February 2016) - Sallander, Jessica; Wallinder, Charlotta; Hallberg, Anders; Åqvist, Johan; Gutiérrez-de-Terán, Hugo
Graphical abstract: Abstract: Agonists of the angiotensin II receptor type 2 (AT2 ), a G-protein coupled receptor, promote tissue protective effects in cardiovascular and renal diseases, while antagonists reduce neuropathic pain. We here report detailed molecular models that explain the AT2 receptor selectivity of our recent series of non-peptide ligands. In addition, minor structural changes of these ligands that provoke different functional activity are rationalized at a molecular level, and related to the selectivity for the different receptor conformations. These findings should pave the way to structure based drug discovery of AT2 receptor ligands.